Research on pressure of shoe upper knitted fabric on forefoot of the woman's instep - Chung, Cao Thị Kiên; Huấn, Bùi Văn (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the method and results of the study on the relationship between elongation, tensile force of shoe upper knitted fabrics and their pressure on the forefoot of women’s instep. The pressure of 5 shoe knitted fabrics on the instep of 10 young women in 4 postures (phase) is measured by the pressure measuring system using Flexscorce A301 sensor of Tekscan. The measured results are compared with the pressure value calculated according to Laplace's. The results of the study show that the pressure value of studied materials on the instep are directly proportional to their elongations and the four measuring postures; the regression equations between the elongation of 5 studied materials and their experimental pressure have a high correlation coefficient (R2 = 0.9955); the regression equation between the material's tensile force and their pressure (to 100 mmHg) on the instep has a relatively high correlation coefficient (R2 = 0.9538). This is an important basis for designing and selecting suitable knitted fabrics to make shoes with good pressure comfort, as well as shoes for diabetics.